Subcapsular hematoma of liver - Rodríguez de Vecchi, Victoriano; Marella, Muzio S (Cirugía del Uruguay, 1973)
This is the presentation of one case of a live.r subcapsular traumatic hematome. The authors remark the peculiar anatomic and clinic aspects of this liver traumatism and make patologic and clinical considerations about this case. They study a radiologic aspect (falling of the right colon angle) which has not been shown in the bibliography making conslderations from surgery point of view.